Pemanfaatan Bio-Economy dari Glycine Max dan Digital Marketing bagi Pengrajin Tempe - Komariyah, Siti; Yuliati, Lilis; Riniati, Riniati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
One of the potentials Jambearum village is from the tempe production which is located in Puger, Jember regency. This potential has the opportunity to be developed into a center for SMEs, because several businesses have joined the "Paguyuban Delima" with the aim of building a forum for communication, friendship, besides a forum for activities to strengthen family functions in an integrated manner, through economically beneficial efforts. However, this potential is constrained by several fundamental problems, including human resources, limited creativity and innovation, marketing, and capital. Aims this research to create innovation of tempeh chips and marketing. To develop business, direct action method through practice is carried out with socialization steps to foster aspects of innovation and creativity. Then marketing is carried out by socialization and introduction to social media methods, sealer, and brand design to market standards while reaching a wider and easier market. The method for capital problems is done by providing direct assistance in the form of a tempe cutting machine. The result shows that a new innovation from tempe products to increase the selling value with the innovation of tempe chip products with various flavors that are packaged and branded in such a way as to attract consumers.